Some approaches to Belief Bases Merge - Falappa, Marcelo Alejandro (2006)
In this work, we de fine some non-prioritized merge operators, that is, operators for the consistent union of belief bases. We de ne some postulates for several kinds of merge operator and we give different constructions: trivial merge, partial meet merge and kernel merge. For some constructions we provide representation theorems linking construction with a set of postulates. Finally, we propose that the formulated operators can be used in some multi-agent systems